Optical spectra of conjugated gold nano-colloids; Scattering cross section and effects of solvent and polydispersity - Ehsan Koushki; Hamid Akherat Doost (Results in Chemistry)
In this paper, a numerical study has been carried out on the effects of the type of solvent and polydispersity of gold nanoparticles (Au NPs) on the absorption and dispersion spectra of its colloidal solution. A theoretical model has been used in which, in addition to considering surface agents, the effect of solvent and polydispersity of the particles can be applied. Different cases were simulated in which the effect of ethylene and methanol alcohol added to the aqueous solution of Au NPs was studied. The refractive index of the mixed solvent was investigated at different percentages of alcohol and at different temperatures. The effect of these factors on the absorption peak which is a result of localized surface plasmon resonance (LSPR) was investigated and it was observed that increasing the refractive index of the solvent (by adding alcohol) can lead to red-shift of the plasmonic peak and the overall increase in the refractive index. Also, effects of polydispersity on the absorption and dispersion curves were studied. To study the optical scattering of Au nano-colloid, the angular dispersion distribution profiles for different hydrodynamic diameters were calculated using the Discrete Dipole Approximation (DDA) model that clearly showed the effect of the hydrodynamic diameter of the target particles on the scattering patterns. The results of this investigation are very important in the interpretation of the absorption spectra of Au NPs, especially the wavelength and width of the plasmonic peak, and through the study of these spectral characteristics, useful information can be obtained about the surface agents and the solvent, which can open a new aperture to sensor applications of Au NPs, such as optical sensors, biomedical imaging and optical communication technologies. These results can be of interest to experimental researchers working in the field of Au NPs and help to interpret spectral data.